ANÁLISE ECONÔMICA E ENERGÉTICA DE FACHADAS FOTOVOLTAICAS NO EXTREMO SUL DO BRASIL - Schlosser, Bruna Schlosser; Freitas, Julye; Cleff, Vinicius; Salamoni, Isabel (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Based on the need to diversify the national energy matrix and minimize the impacts caused by non-renewable sources of energy, renewable sources are gaining space by contributing to energy demand. In this context, photovoltaic (PV) energy comes with a great potential to adapt to urban environments by integrating itself, into the envelope of buildings. This work aims to evaluate the economic and energy potential of the use of PV solar modules integrated in the façade of a commercial building in the city of Pelotas by replacing the coating materials used in the building (reflective glass and modified aluminum composite - ACM). Three models of PV integration in the building were proposed and for the analysis of investments, Net Present Value (NPV) and Internal Modified Return Rate (IRR-m) parameters were used as methods of investment feasibility analysis. The results show that depending on the integration model used all the energy demand of the building is supplied and in the best case the energy production by the modules supplies 97% of the demand. In the economic feasibility study, the investment return time is, in the best case, approximately 1.5 years.